E-booking system for endoscopy training lists enhances their utilisation. (13th March 2011) - Walker, N A Faure; McNair, A; Beale, A; Greenwood, R; Blazeby, J M
Abstract : Introduction: Provision of dedicated training lists is a key criterion of the Global Rating scale ('GRS') training domain for Joint Advisory Group on GI Endoscopy ('JAG'). Extra time within training lists allows endoscopy supervision but full utilisation of lists is necessary to avoid wastage. Changes in trainees' work patterns makes regular attendance at training lists difficult. The aim of this study was to optimise the use of dedicated endoscopy training lists with an electronic booking system. Prior to the new system, trainees attended lists haphazardly. With the new system, trainees booked training lists on line in advance for a suitable time. Methods: Attendance was confirmed by the endoscopy reporting system and validated by comparing two trainees' logbooks. Medical and surgical endoscopy training lists were audited in 2007/08 for 24 months, and in 2010 for 4 months following introduction of the booking system. Utilisation was calculated as the number of 'points' used by trainees divided by the total points available for the training lists. (Training lists have 16 'points' and non training (service lists) have up to 24 points. Gastroscopy and flexible sigmoidoscopy have 2 points, colonoscopy 4 points, upper GI EUS 5 points and an ERCP 6 points.) Results: In 2007/08, 12 trainees performed 677 procedures, equivalent to 1858 points, with 874 points (47.0%) on training lists and 984 (53.0%) on non-training lists. Training lists were 874/4928 (17.7%) utilised (95% CI 16.6%>18.8%). In 2010, 10 trainees performed 276 procedures (766 points) in the 4 months after introduction of the electronic booking system. 498 points (65.0%) were on training and 268 (35.0%) were on non-training lists. The lists were 498/816 (61.0%) utilised in 2010 (95% CI 57.6%> 64.4%). The most significant improvements in utilisation were seen in upper GI and medical training lists, which increased from 32/1616 (2.0%) and 180/1632 (11.0%) in 2007/08 to 132/272 (48.5%) and 248/272 (91.2%) in 2010. Conclusion: The electronic booking system improved attendance at dedicated training lists from 17.7% in 2007/08 to 61.0% in 2010. The system also improved the proportion of training done on allocated training lists rather than service lists from 47.0% in 2007/08 to 65.0% in 2010. The most significant improvements were seen in medical and upper GI lists. Such booking systems can help trainees to obtain competencies within shift systems and reduce pressure on endoscopy services.